Purpose of the creation of man: Quran’s true version of anthropic principle - Javed Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Scientists, especially theoretical physicists and cosmological philosophers have always wondered the beauty of the universe, especially how it has led to the creation or evolution of intelligent beings like us. There is a certain, wondrous beauty in the underlying plan. This question has become the topic of an interesting debate: What is our place in the Universe and was the Universe made for us? These debates have more often than not been influenced by the dominant philosophies of life in the contemporary world, often pushed by the dominant political and economic forces. As the last few centuries have been dominated by the atheistic or agnostic philosophies, Anthropic Principle has been defined in a way suitable for the forces. Quran, the Holy Book of Islam, on the other hand, presents a different version of the questions related to Anthropic Principle, which describes a specific purpose of the creation of man, his relationship with God and the Universe. This has been named “True Anthropic Principle” by the author of this paper.